Revision shoulder arthroplasty for failed humeral head resurfacing hemiarthroplasty. (July 2019) - Thangarajah, Tanujan; Ajami, Sara; Coathup, Melanie; Blunn, Gordon W.; Higgs, Deborah; Falworth, Mark; Lambert, Simon
Background: The purpose of the present study was to analyze and report the clinical outcomes following revision shoulder arthroplasty for failed humeral head resurfacing hemiarthroplasty (HHRH). Methods: All patients who underwent revision shoulder arthroplasty for failed HHRH at our institution were retrospectively reviewed. Twenty-two shoulders in 20 patients were available for analysis. Mean age at the time of HHRH was 60 years (range 42 years to 75 years). The cohort consisted of 17 females and three males. Results: The mean time from HHRH to revision was 5 years (range 1 year to 8 years). Mean age at the time of revision surgery was 62 years (range 44 years to 80 years). Patients were followed-up for a mean of 3.3 years (range 2 years to 4 years) after revision. Following revision surgery, there was an increase in forward elevation from 67° (range 0° to 130°) to 97° (range 40° to 160°) ( p = 0.04). This was accompanied by an improvement in both the Oxford Shoulder Score and the subjective shoulder value, which increased from 13 (range 2 to 28) to 39 (range 24 to 48) ( p = 0.000) and from 23 (range 0 to 65) to 79 (range 25 to 100) ( p = 0.000) respectively. Conclusions: Revision shoulder arthroplasty for failed HHRH improves functional outcome.